Antibiotic Effects on Microbial Community Characteristics in Soils under Conservation Management Practices. Issue 1 (26th November 2012) - Unger, Irene M.; Goyne, Keith W.; Kennedy, Ann C.; Kremer, Robert J.; McLain, Jean E.T.; Williams, Clinton F.
Abstract : Veterinary antibiotics (VAs) administered to livestock are introduced to agroecosystems via land application of manure, posing a potential human and environmental health risk. Recent evidence suggests that agroforestry and grass vegetative filter strips (VFS) may act to mitigate VA transport or enhance VA degradation; however, VAs may adversely affect soil microbial communities within VFS and thus alter the primary functioning of the VFS. The objectives of this research were to investigate potential changes in microbial community structure and function and to quantify the development of antibiotic resistance in VFS and no‐till soils exposed to various VA classes and concentrations. Laboratory mesocosms were established using soils collected from no‐till cropland and two VFS (grass and agroforestry). Soils were treated with oxytetracycline or lincomycin (5–200 mg kg −1 soil). Individual mesocosms underwent destructive sampling at nine time points during 63 d, and the soils were tested for soil microbial function (C‐utilization, dehydrogenase, and fluorescein diacetate hydrolysis assays), community structure (phospholipid fatty acid analysis), and antibiotic resistance. Functional assays associated with all VA treatments showed an initial inhibitory effect, but this trend was generally reversed by the seventh day. Shifts in microbial community structure and increased antibiotic resistance were not observed, suggesting that the soil microbial communities were robust to the effects of oxytetracycline and lincomycin at test concentrations. This work indicates that using VFS to mitigate VA loss from agroecosystems will not diminish important primary functions associated with VFS use in agriculture.